Development of video learning media based on powtoon application on the concept of the properties of light for elementary school students - Anisa Khayati Nur Kafah; Lukman Nulhakim; Aan Subhan Pamungkas (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2020)
The purpose of this research is to know the process of development and feasibility of the learning media of Powtoon and analyze student's understanding after using media in the learning. This research is research and development, the models of construction adopted by Borg and Gall. The product is tested for eligibility through validation testing by the content and media experts. The subject of this study was a student of class IV SDN 3 Attack as much as 20 students. Based on the analysis of the data acquired that a learning-based media of Powtoon is declared feasible by the media experts with an average percentage score of 88% and content expert with a percentage of 80%. the response of students with a rate of 98% the which included "excellent," as well as  test of student's understanding, gained an average of scores of 89.25, which belongs to the category of "excellent." From the study, it can to be concluded that learning deserves media of powtoon use in the learning process on the property of light topic.